Community-based education using tempeh nugget modules to increase plant-based protein consumption in preventing stunting - Susianto, Susianto; Mamlukah, Mamlukah (Jurnal Konseling dan Pendidikan, 2024)
Stunting remains a serious public health issue in Indonesia, including in Karangmuncang Village, Cigandamekar District, Kuningan Regency. One potential solution to this nutritional problem is increasing the consumption of plant-based foods, such as tempeh. This study aims to evaluate the effectiveness of an educational module based on tempeh nuggets in increasing plant-based protein consumption among housewives with children under five in Karangmuncang. The research used a quasi-experimental design with pre-test and post-test, involving 60 randomly selected respondents. The research instrument consisted of a questionnaire with five main sections: demographic data (age, education, employment, number of children, family income), knowledge about plant-based foods (definition, sources, benefits, and their role in preventing stunting), attitudes toward plant-based consumption (confidence, willingness to try tempeh, and perception of food variety), plant-based consumption behavior (frequency, processing method, and frequency of cooking tempeh), and acceptance of tempeh nuggets (interest, taste assessment, routine consumption plan, and perception of benefits). After four weeks of educational intervention, data were analyzed using the paired T-test for knowledge, the Wilcoxon Signed-Rank test for attitudes and acceptance, and the Chi-Square test for tempeh consumption behavior. The results showed a significant increase in knowledge, attitudes, consumption behavior, and acceptance of tempeh nuggets (p < 0.05). These findings suggest that the educational module effectively increases awareness and adoption of plant-based protein foods in the community. Future research should involve larger sample sizes, extended intervention periods, and explore other factors influencing behavior change.